2021
DOI: 10.1016/j.celrep.2021.109515
|View full text |Cite
|
Sign up to set email alerts
|

NGPF2 triggers synaptic scaling up through ALK-LIMK-cofilin-mediated mechanisms

Abstract: Highlights d Activity blockade by TTX induces rapid and transient release of NGPF2 d NGPF2 is necessary and sufficient for synaptic scaling up d NGPF2 triggers synaptic scaling up through ALK-LIMKcofilin pathway d NGPF2 synthesis requires FMRP1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 70 publications
(85 reference statements)
0
6
0
Order By: Relevance
“…Neuroinflammation is thought to contribute to aging and age-related cognitive impairment by damaging hippocampal synaptic function ( Vanguilder and Freeman, 2011 ; Bettio et al, 2017 ; Juan and Adlard, 2019 ). The neurite growth-promoting factor 2 (NGPF2; also referred to as midkine) is not only a cytokine but also a neurotrophic factor ( Ross-Munro et al, 2020 ; Zhou et al, 2021 ). It is principally expressed in the developing central nervous system (CNS; Zhou et al, 2021 ) and is usually reduced to negligible level in adulthood ( Yoshida et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neuroinflammation is thought to contribute to aging and age-related cognitive impairment by damaging hippocampal synaptic function ( Vanguilder and Freeman, 2011 ; Bettio et al, 2017 ; Juan and Adlard, 2019 ). The neurite growth-promoting factor 2 (NGPF2; also referred to as midkine) is not only a cytokine but also a neurotrophic factor ( Ross-Munro et al, 2020 ; Zhou et al, 2021 ). It is principally expressed in the developing central nervous system (CNS; Zhou et al, 2021 ) and is usually reduced to negligible level in adulthood ( Yoshida et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…The neurite growth-promoting factor 2 (NGPF2; also referred to as midkine) is not only a cytokine but also a neurotrophic factor ( Ross-Munro et al, 2020 ; Zhou et al, 2021 ). It is principally expressed in the developing central nervous system (CNS; Zhou et al, 2021 ) and is usually reduced to negligible level in adulthood ( Yoshida et al, 2014 ). However, mounting evidence indicates that NGPF2 is markedly upregulated in many pathological conditions that are characterized by inflammatory injury.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that in single mutant adults, compensatory mechanisms such as re‐wiring of neuronal circuits can overcome the severity of the defect. It is also possible that there are Igf1‐r independent, but redundant Ltk/Alk pathways that result in the behavioral defects only observed in the DKOs, such as the recently reported ALK‐LIMK‐cofilin pathway, which regulates synaptic scaling (Zhou et al , 2021). Interestingly, in the Golgi‐stained sections (Fig 3E), we noticed that there appeared to be a reduction in the number of dendritic spines in DKO versus WT mice.…”
Section: Discussionmentioning
confidence: 99%
“…NRG1 deficiency or CRD-NRG1 overexpression in cortical projection neurons results in enhanced GABAergic inhibitory neurotransmission, thereby causing imbalance of excitatory-Inhibitory neurotransmission and altered LTP ( Agarwal et al, 2014 ). Nevertheless, one possibility that NRG1 regulates LTP through an excitatory neuron-intrinsic mechanism cannot be excluded, as a recent study reported that overexpression of NRG1 in forebrain excitatory neuron in ctoNrg1 mice that mimic the upregulated level of NRG1 in schizophrenic patients, results in decreased spine density and impaired glutamatergic neurotransmission in hippocampus CA1 and PFC via activation of LIMK1 and subsequent inactivation of p-cofilin ( Chen et al, 2021 ), which are essential for AMPAR stabilization at synapse and various forms of synaptic plasticity ( Ben Zablah et al, 2021 , Zhou et al, 2021 ).…”
Section: Schizophrenia Risk Genes Play Essential Roles In Synaptic Pl...mentioning
confidence: 99%